PRODUKTIFITAS KECAMATAN DALAM BIDANG PERTANIAN DI KABUPATEN KEBUMEN (Evaluasi Efisiensi dan Efektifitas dengan menggunakan DEA) - to, Surip (Pusjar SKPP Lembaga Administrasi Negara, 2010)
Kebumen is an agricultural area in Central Java Province. Indicator is shown by the number of farmers as much as > 50% of total population and agricultural sector's contribution to the economy of region as big as 34.71%. The contribution of the agricultural sector is interesting to know the productivity of agriculture in each district. This paper uses Data Envelopment Analysis tool Banker-Charnes-Cooper (DEA-BCC) input in measuring productivity in the agricultural district. Analysis results show that as many as four districts efficiently and twenty-two districts are inefficient.